2017
DOI: 10.1542/peds.2016-4258
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Closure of Patent Ductus Arteriosus in Infants ≤1500 g

Abstract: The likelihood of PDA spontaneous closure in VLBW infants is extremely high. We provide in our findings a platform for future placebo-controlled trials focused on the smallest and youngest infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 24 publications
8
115
1
2
Order By: Relevance
“…Semberova et al recently illustrated spontaneous ductal closure in the majority of preterm neonates prior to discharge, with incidence of PDA inversely related to gestational age, in a cohort of infants managed with a conservative approach. While the duration of ductal patency increased with decreasing gestational age, with a median age at ductal closure of 71 days in patients <26 weeks of GA, they identified no significantly increased risk of morbidities such as BPD or NEC (Figure ) . These studies illustrate the concept that nonintervention does not appear to lead to increased morbidity or mortality.…”
Section: Experience With Noninterventional Strategiesmentioning
confidence: 88%
See 2 more Smart Citations
“…Semberova et al recently illustrated spontaneous ductal closure in the majority of preterm neonates prior to discharge, with incidence of PDA inversely related to gestational age, in a cohort of infants managed with a conservative approach. While the duration of ductal patency increased with decreasing gestational age, with a median age at ductal closure of 71 days in patients <26 weeks of GA, they identified no significantly increased risk of morbidities such as BPD or NEC (Figure ) . These studies illustrate the concept that nonintervention does not appear to lead to increased morbidity or mortality.…”
Section: Experience With Noninterventional Strategiesmentioning
confidence: 88%
“…Because of the widely held belief that treatment is beneficial, and therefore necessary, that natural history has been obscured by a lack of data on the trajectories of untreated preterm infants. Several recent studies, now including more than 1000 infants managed conservatively, have described the consequences of adoption of nonintervention strategies at individual centers . With few exceptions, studies have not demonstrated an increased risk of morbidity or mortality in association with marked reduction or elimination of use of medical or surgical intervention to close the ductus.…”
Section: Experience With Noninterventional Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using conservative treatment, Koch et al noted that 34% of extremely premature infants underwent spontaneous PDA closure by 8 postnatal days, while Rolland et al reported that 73% of extremely premature infants closed their PDAs by 165 days . Furthermore, Semberova et al reported that among 280 VLBW (<1500 g) infants receiving conservative treatment for PDA and followed with consecutive echocardiography, 85% underwent spontaneous ductal closure prior to hospital discharge …”
Section: Percutaneous Closure Vs Conservative Managementmentioning
confidence: 99%
“…Infants born during the canalicular stage of lung development, in addition to having an increased risk of developing BPD, are also at high risk for prolonged PDA. Spontaneous closure of the PDA occurs at a median of 13 days in infants born in the 26th and 27th weeks and a median of 71 days in infants born prior to 26 weeks . Therefore, an hsPDA is often most present during the time when a premature infant is also most susceptible to lung injury leading to BPD.…”
Section: Hemodynamically Significant Pda and Bpdmentioning
confidence: 99%